Studi Dan Evaluasi Setting Relai Arus Lebih Pada Transformator Daya Di Gardu Induk Garuda Sakti Pekanbaru - Arif, Muhammad; Firdaus, Firdaus (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
At the substation Garuda Sakti there are four power transformer units that is 2 units of 60 MVA and 50 MVA 2 units that supply power to the entire territory of Pekanbaru. Needed a reliable protection system to overcome the problems, including short circuit and overload disorders. The amount of short circuit current that may occur on an electrical system needs to be known before the actual disturbance occurred. Therefore it is necessary to set the relay overcurrent (OCR) is good so that the relay can protect electrical equipment from current short circuit or overload.Keyword : OCR